PENGEMBANGAN DAN VALIDASI INSTRUMEN KETERAMPILAN PEMECAHAN MASALAH BERBASIS SOCIO-SCIENTIFIC ISSUE TERINTEGRASI METAKOGNITIF MENGGUNAKAN RASCH MODEL - Vira Veronika; Woro Setyarsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Problem-solving skills are essential twenty-first-century competencies that students need to develop. However, assessment instruments commonly used in schools primarily focus on learning outcomes and have not comprehensively measured students' thinking processes and metacognitive regulation. This study aimed to develop a Socio-Scientific Issue (SSI)-based problem-solving skills assessment instrument integrated with metacognitive aspects on the topic of work and energy, as well as to examine its validity, reliability, item difficulty, discriminating power, and students' problem-solving skills profile. This study employed a Research and Development (R&D) approach using the ADDIE model. The limited trial involved 33 students, while the large-scale trial involved 103 tenth-grade students of SMA YPM 2 Sukodono Sidoarjo. The data were analyzed using the Percentage of Agreement (PoA), the Rasch Model with the assistance of Winsteps software, and descriptive analysis. The results indicated that the developed instrument possessed excellent validity, with PoA values of 97.67% for content validity, 100% for construct validity, and 97.22% for language validity. Sixteen out of twenty items were empirically validated. The instrument satisfied the unidimensionality requirement, with a Raw Variance Explained by Measures value of 69.5%, and demonstrated excellent reliability, with a Cronbach's Alpha of 0.88, Person Reliability of 0.86, and Item Reliability of 0.96. The instrument also exhibited varied levels of item difficulty, good discriminating power, and indicated that students' problem-solving skills were generally at a moderate level. Therefore, the developed instrument is suitable for assessing SSI-based problem-solving skills integrated with metacognitive aspects.